Alternatif Penyelesaian Sengketa Dalam Perjanjian Pemberian Hibah Pemerintah Indonesia Kepada Pemerintah Asing - Gayo, Anggie Artha; Sadiawati, Diani; Haryanto, Imam (Universitas Semarang, 2024)
This research aims to examine the clause of the choice of law and forum in Indonesian grant agreement to foreign government based on Government Regulation 48 of 2018 as amended by Government Regulation 57 of 2019 (Grant Regulation). Issues frequently arise arise in grant agreements, specifically grant recipients' rejection of these clauses, which impedes grant implementation. The grant has a purpose as a tool of diplomacy, which is a form of public relations. In contrast, the grant agreements within the Grant Regulation contradictorily possess characteristics of civil relations due to the obligation to include the choice of law, the national law of the Republic of Indonesia, and the choice of forum in the Central Jakarta District Court. This research introduces novelty by presenting a perspective hitherto unexplored in previous studies. Most prior research has predominantly focused on the urgency of Indonesian grants before enacting the Grant Regulation, with no specific study dedicated to examining grant agreements regulated by this regulation. The research findings conclude that there needs to be more consistency between the objectives of the grant and the nature of the agreements stipulated in the Grant Regulation. Therefore, adjustments to the provisions of the Grant Regulation are deemed necessary transforming the substansce of grant agreement from civil relations to public relations by incorporating the choice of law and forum clauses in the grant agreements by the provisions applicable in international law. Penelitian ini bertujuan untuk mengkaji ketentuan klausul pilihan hukum dan pilihan forum dalam perjanjian hibah Indonesia kepada Pemerintah Asing berdasarkan Peraturan Pemerintah Nomor 48 Tahun 2018 sebagaimana diubah dengan PP Nomor 57 Tahun 2019 (PP Hibah). Permasalahan yang seringkali muncul terkait perjanjian hibah adalah penolakan oleh penerima hibah terhadap klausul tersebut, yang pada akhirnya menghambat kelancaran proses hibah. Hibah Indonesia berfungsi sebagai alat diplomasi yang memiliki karakteristik hubungan publik, sementara perjanjian hibah dalam PP Hibah memiliki karakteristik yang kontradiktif yakni hubungan perdata dengan adanya kewajiban perjanjian yang memuat pilihan hukum, hukum nasional Republik Indonesia, dan tempat penyelesaian sengketa di PN Jakarta Pusat. Penelitian ini memiliki kebaruan karena menghadirkan perspektif yang belum pernah dibahas oleh penelitian terdahulu. Sebagian besar penelitian terdahulu hanya membahas urgensi hibah Indonesia sebelum adanya PP Hibah, dan belum ada penelitian yang secara khusus mengkaji perjanjian hibah yang diatur dalam PP Hibah. Hasil penelitian menyimpulkan bahwa terdapat ketidaksesuaian antara tujuan hibah dengan sifat perjanjian yang diatur dalam PP Hibah. Oleh karena itu, diperlukan penyesuaian terhadap ketentuan PP Hibah dengan mengubah substansi sifat perjanjian hibah menjadi hubungan publik dengan menggunakan klausul pilihan hukum dan pilihan forum dalam perjanjian hibah sesuai ketentuan yang berlaku di hukum internasional.